IMPLEMENTASI PROGRAM TAḤFĪẒ AL-QUR'ĀN DI SEKOLAH SEBAGAI UPAYA UNTUK MENINGKATKAN MUTU PEMBELAJARAN PAI - Tia Khotifah, - (2022)
This research was motivated by the understanding that emerged among public school students who considered learning the Qur'an only for madrasas, due to the different hours of PAI subject matter. This reason is a factor that causes the interaction between students and the Qur'an to decrease and even the students' ability to recite it is not maximal. Therefore, this research is expected to contribute to describing best practice programs in order to provide understanding and habituation for students to interact intensively with the Koran through programs organized by public schools and to be part of efforts to improve the quality of learning. The purpose of this study is to describe: (1) planning the tafīẓ al-Qur'ān program; (2) the implementation of the tafīẓ al-Qur'ān program and (3) the evaluation of the tafīẓ al-Qur'ān program as an effort to improve the quality of PAI learning. This study uses a qualitative approach with a descriptive method. Data was collected through interviews, documentation studies and observations. This research was conducted in a school located in Bogor Regency with the research subjects namely the tafīẓ coordinator, taf supervisor and students. The results of the research are: (1) the planning of the tafīẓ program includes the formulation of objectives, curriculum, parties involved and the formation of tafīẓ groups; (2) the implementation of the taḥfīẓ program includes the realization of scheduling, stages of guidance, methods, media and strategies used, students' efforts to maintain their memorization, supporting and inhibiting factors and the role of the program on the quality of PAI learning; (3) the evaluation of the tafīẓ program includes a weekly evaluation, the taf exam which is conducted in stages and the final results of the taf in the form of a report card.